2008
DOI: 10.1161/hypertensionaha.107.101188
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II and Cardiomyopathy in End-Stage Renal Disease

Abstract: Abstract-Circulating urotensin (UTN) is increased in patients with heart failure and in patients with renal diseases, and UTN antagonism is currently considered as a potential treatment for these conditions. Contrary to this contention, studies in end-stage renal disease suggest that, perhaps because of interference with sympathetic and NO systems, UTN may be cardioprotective. (UTN) is a cyclic undecapeptide that is widely distributed in several organ systems, including the vascular system and the heart. 1 UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Conflicting results have been reported by researchers measuring blood values of UII in patients with kidney disease. Some studies observed a lower UII concentration among subjects with CKD and ESRD whereas other studies reported higher UII concentration in patients with kidney disease [16,17]. We found that UII is significantly lower in our current study, and this is consistent with Mosenkis, et al's results [18] but differs from that of Tostune, et al [8,9].…”
Section: Multiple Regression Analysis Of Circulating Irisin With Othesupporting
confidence: 90%
“…Conflicting results have been reported by researchers measuring blood values of UII in patients with kidney disease. Some studies observed a lower UII concentration among subjects with CKD and ESRD whereas other studies reported higher UII concentration in patients with kidney disease [16,17]. We found that UII is significantly lower in our current study, and this is consistent with Mosenkis, et al's results [18] but differs from that of Tostune, et al [8,9].…”
Section: Multiple Regression Analysis Of Circulating Irisin With Othesupporting
confidence: 90%
“…However, in these patients, plasma UII levels were inversely correlated to many neurohormonal factors (84), to biomarkers of atherosclerosis, and to endothelial activation (83). Furthermore, elevated UII levels are associated with more favorable echocardiographic profiles (154) and actually predict lower overall cardiovascular risk in ESRD (155). These paradoxical findings hint at a potential protective role of UII in some forms of renal disease.…”
Section: Pathological Significance Of Uiimentioning
confidence: 99%
“…These paradoxical findings hint at a potential protective role of UII in some forms of renal disease. This role is thought to stem from the interference of UII with sympathetic and NO systems (154).…”
Section: Pathological Significance Of Uiimentioning
confidence: 99%
“…UII stimulates endothelial cell and smooth muscle cell proliferation. Although UII and GPR14 levels were found to be increased in the blood of diabetic patients with nephropathy [13] , their roles in the renal fibrogenesis under any conditions remain lack of direct evidence. We provide here the first evidence for the increased expression of UII mRNA and protein in the rat of the UUO rats.…”
Section: E Effects Of Uii On Ecmmentioning
confidence: 98%